Buccal health promotion in students and workers administrative service of the medicine faculty the San Marcos university. - Maita Veliz, Luis V. (2006)
The promotion of the health is a process that give to the people the instruments to lead a better control for the health care. In this process participing the patients, the family, the community, the heath services and the autority`s health. There is a little information about the promotion of the dental health at the San Marcos University. The results show that thre is not an effective program of dental diseases prevention whitin the students and workers of the Faculty of Medicine at San Marcos University.